2023
DOI: 10.3390/ijms24098422
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis in Immuno-Oncology

Abstract: The complexity of the cellular and non-cellular milieu surrounding human tumors plays a decisive role in the course and outcome of disease. The high variability in the distribution of the immune and non-immune compartments within the tumor microenvironments (TME) among different patients governs the mode of their response or resistance to current immunotherapeutic approaches. Through deciphering this diversity, one can tailor patients’ management to meet an individual’s needs. Single-cell (sc) omics technologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 126 publications
0
5
0
Order By: Relevance
“…Moreover, scRNA-seq facilitates the discovery of novel biomarkers beyond traditional approaches. For instance, circulating tumor cells (CTCs) and immune cells in the bloodstream harbor valuable information reflecting tumor dynamics and therapy response ( 74 , 75 ). Recent studies have identified specific cell subsets, such as B cell clones and monocyte phenotypes, associated with improved survival and therapy response in melanoma patients undergoing ICI treatment ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, scRNA-seq facilitates the discovery of novel biomarkers beyond traditional approaches. For instance, circulating tumor cells (CTCs) and immune cells in the bloodstream harbor valuable information reflecting tumor dynamics and therapy response ( 74 , 75 ). Recent studies have identified specific cell subsets, such as B cell clones and monocyte phenotypes, associated with improved survival and therapy response in melanoma patients undergoing ICI treatment ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tailoring immunotherapeutic strategies for BC management involves developing patient-specific approaches [25]. This is achieved by taking into account individual immune profiles, genomic alterations, and tumor characteristics [257]. Moreover, investigating the mechanisms behind resistance that may develop in response to immunotherapy is essential.…”
Section: Biomarkers and Future Directionsmentioning
confidence: 99%
“…While traditional techniques allow for the quantitative profiling of genomic, transcriptomic, and proteomic signatures in bulk tumors, the advent of single-cell sequencing has catalyzed significant advancements in identifying innovative biomarkers, novel cellular phenotypes, and new therapeutic targets that remain undetectable through bulk-sequencing approaches [43][44][45] (Figure 1A). Despite a limited sensitivity to detect low-abundance RNAs and "technical noise" due to the low amount of input material [46,47], single-cell sequencing, with its high resolution, serves as an invaluable tool for studying the properties of immune cells. This includes exploring diverse developmental lineages, antigen specificity, phenotypic plasticity, cellular transitions, interactions, cellular communications, and adaptability to various microenvironments [45,[48][49][50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%